Proceedings of the 2019 27th ACM Joint Meeting on European Software Engineering Conference and Symposium on the Foundations of 2019
DOI: 10.1145/3338906.3341181
|View full text |Cite
|
Sign up to set email alerts
|

Eagle: a team practices audit framework for agile software development

Abstract: Agile/XP (Extreme Programming) software teams are expected to follow a number of specific practices in each iteration, such as estimating the effort ("points") required to complete user stories, properly using branches and pull requests to coordinate merging multiple contributors' code, having frequent "standups" to keep all team members in sync, and conducting retrospectives to identify areas of improvement for future iterations. We combine two observations in developing a methodology and tools to help teams … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 7 publications
4
8
0
Order By: Relevance
“…Another study related to auditing agile projects was done by Gibbons [20], who created a framework to audit the agile teams focused on the XP environment. The framework monitors agile teams on adherence to agile practices during solution development and backlog delivery.…”
Section: H Agile Project Auditingmentioning
confidence: 99%
See 3 more Smart Citations
“…Another study related to auditing agile projects was done by Gibbons [20], who created a framework to audit the agile teams focused on the XP environment. The framework monitors agile teams on adherence to agile practices during solution development and backlog delivery.…”
Section: H Agile Project Auditingmentioning
confidence: 99%
“…The assessment of specific papers on auditing agile project found that the first published papers were in year 2013 [25], [35]. Other publications found in year 2018 [34] and 2019 [3], [14], [20], [36], [41]. A total of eight papers were published on auditing agile projects from 2013 to 2019.…”
Section: Phase 2: Extensive Reading and Categorizing Of The Selected mentioning
confidence: 99%
See 2 more Smart Citations
“…• Gave students access to a new metrics dashboard that was different from the one used previously. We made this change migrating the dashboard to a new platform [12]. The new dashboard presented a similar set of metrics about Backlog, CI, and TDD as the previous one.…”
Section: Case Studymentioning
confidence: 99%